THE EFFECT OF MURABAHAH AND ISTISHNA FINANCING ON NET PROFIT WITH TPF AS A MODERATING VARIABLE IN ISLAMIC COMMERCIAL BANKS FOR THE 2018-2020 PERIOD - Zahraa Ar Rumaishaa; R. Mohd Zamzami (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to examine and analyze the effect of murabahah and istishna financing on net income with third party funds as a moderating variable. The population of this study is Islamic commercial banks registered with the Financial Services Authority (OJK) in 2018-2020. The sampling method used was purposive sampling and obtained 3 companies in this sample consisting of Bukopin Syariah Bank, Jabar Banten Syariah Bank, and Muamalat Indonesia Bank. Data analysis in this study used panel data regression analysis using the Eviews 10 software. The results showed that murabahah financing had a positive effect on net income, while istishna financing had no effect on net income. The use of moderating variables of third party funds is able to moderate by weakening the effect of istishna financing on net income while murabahah financing cannot be moderated by third party funds. Simultaneously, murabahah and istishna financing have a positive and significant effect on net income. In this study, the independent variable can affect 40.9316% of net income while 59.0684% is influenced by variations of other variables that are not included in this study.